2001
DOI: 10.1348/000709901158451
|View full text |Cite
|
Sign up to set email alerts
|

Students’ and teachers’ cognitions about good teachers

Abstract: The research method of collecting free essays and utilising correspondence analysis to represent conceptual items and groups of participants seems promising as long as a theoretical framework is available to interpret the resulting representation of similarities between items and groups of participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
1
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 21 publications
6
83
1
10
Order By: Relevance
“…These attributes were considered more important than Rapport and second only to Delivery. This is contrary to findings in other contexts which indicated that students placed higher importance on rapport attributes than on knowledge and credibility attributes (Beishuizen, Hof, van Putten, Bouwmeester, & Asscher, 2001;Clayson, 2005). However, the priority and high importance placed on knowledge of the target language and teacher qualifications is supported by Park and Lee (2006), which is the only other publication we have been able to locate which explores the importance of this attribute in a Korean context and which is based on rigorous quantitative research.…”
Section: Discussioncontrasting
confidence: 99%
“…These attributes were considered more important than Rapport and second only to Delivery. This is contrary to findings in other contexts which indicated that students placed higher importance on rapport attributes than on knowledge and credibility attributes (Beishuizen, Hof, van Putten, Bouwmeester, & Asscher, 2001;Clayson, 2005). However, the priority and high importance placed on knowledge of the target language and teacher qualifications is supported by Park and Lee (2006), which is the only other publication we have been able to locate which explores the importance of this attribute in a Korean context and which is based on rigorous quantitative research.…”
Section: Discussioncontrasting
confidence: 99%
“…Third, interpersonal and affective aspects are very important when students evaluate their teacher or the course created by their teacher (Johannessen et al 2002). For secondary school students, being a good teacher is almost equivalent to establishing good personal relationships with students (Beishuizen et al 2001). Adolescent students feel a strong need to be supported, understood, and listened to (Blanco et al 2002).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…He should be in good terms with his colleagues 10. He is willing to take up extra duties with pleasure [12] In 2000 s, the duality of the theories was regarded as a way to organize good teachers' characteristics remained in the work by Beishuizen et al The authors introduced the notions of the Personality View and the Ability View [13]. The Personality View identifies personality components and emphasizes that a good teacher has balanced and mature personality with characteristics such as kindness and enthusiasm.…”
Section: Scientific Literature Reviewmentioning
confidence: 99%